Impact of premenstrual syndrome and premenstrual dysphoric disorder on maternal antenatal depression. - Nozomi Ihara; Yoko Sato; Subaru Ikeda; Hiromi Matsufuji; Kimiyo Kikuchi; Yoshiko Suetsugu; Naoko Hikita; Seiichi Morokuma (PLoS ONE)
In this study, we aimed to determine the association of premenstrual syndrome (PMS) or premenstrual dysphoric disorder (PMDD) with maternal antenatal depression. This cross-sectional, online questionnaire-based observational study included 212 pregnant women between gestational ages 24 weeks and 28 weeks 6 days. PMS and PMDD were measured using the PMDD Scale, and maternal antenatal depression was evaluated using the Edinburgh Postnatal Depression Scale. Baseline characteristics, clinical information, and associated factors were also included in the questionnaire. Analyses were conducted using a binomial logistic regression model with Edinburgh Postnatal Depression Scale positivity (maternal antenatal depression) as the dependent variable. Having "PMDD" (odds ratio: 3.54 [95% confidence interval: 1.26-9.93], p = 0.02) and "PMS" (odds ratio 2.31 [1.10-4.87], p = 0.03) on the PMDD rating scale were significantly associated with maternal antenatal depression. Therefore, our results suggest that screening for a history of PMS or PMDD during the early antepartum interview may aid mental health care and prevent perinatal depression during the early stages of pregnancy.